The Role of Slang Words in Enhancing Informal English Communication Skills - Firmansyah, M. Arjun Khoirudin; Zainuddin, M.; Lestari, Iin Widya (Universitas Sulawesi Barat, 2024)
Slang represents a dynamic and informal aspect of language, often reflecting cultural identity and creativity. This study examines the types and meanings of slang words used in six episodes of the Wednesday series (2022), aiming to explore their linguistic and pedagogical significance. Using a qualitative descriptive approach based on Miles and Huberman’s content analysis framework, the study categorizes slang words into four types: coinage, blending, clipping, and acronyms. Coinage emerged as the most frequently used type, contributing to the series' authenticity and narrative depth, while blending, clipping, and acronyms provided linguistic variety. The findings highlight the potential of popular media as a resource for EFL learning, offering learners exposure to authentic informal communication. Slang enhances vocabulary acquisition, listening comprehension, and cultural understanding, making it a valuable tool for bridging formal education and real-world language use. However, the study’s scope is limited to six episodes, leaving room for future research to explore additional contexts and pedagogical outcomes. This research underscores the relevance of incorporating media into language instruction, providing practical insights for educators and learners. By analyzing the interplay between slang and media, the study contributes to applied linguistics and supports innovative approaches in EFL pedagogy.